The photo-dramatics of atọ́ka photoplay magazine (2014)
The photo-dramatics of Atoka implies the various dramaturgical devices employed in creating Atoka photoplay magazine. The composition of the photoplay magazine relies extensively on the editorial and creative ingenuity of Olotuu (editor) who controls the three-modal arts of Atoka, namely: dramatic art, photographic art and publishing art. Atoka tells its stories primarily in photographs, hence series of artistic and technical manipulations to convey its dramatic story vividly to its readers. This paper which adopts Roland Barthe‟s photo-semiotics examines the photo-dramatics of Atoka, dwelling on its various dramaturgical devices of adaptation techniques; photographic shots, shots imposition and continuous dialogue; editorial intervention: speech balloons, thought bubbles, and cap prints; and intro and recap devices.